Assessment of hydrocarbons for gasoline surrogate: An optimization study. (15th November 2022) - Kim, Doohyun; Song, Jeongwoo; Song, Hwasup; Lim, Yunsung; Lee, Sanguk; Song, Han Ho
Highlights: 19 new hydrocarbons are assessed for future use in gasoline surrogate development. Surrogate optimization approach is utilized for assessment. Expanding iso -alkane representation to cover C5 -C10 is the most effective approach. Iso -alkane, cycloalkane, aromatic species with favorable properties are identified. Updated palette generates improved property emulation for various gasoline batches. Abstract: A fuel surrogate is a model fuel that replicates combustion phenomena of real transportation fuels within computational framework. Successful surrogate formulation would be emulating multiple physical and chemical properties that are most influential to combustion characteristics using a minimum number of surrogate components. To achieve this goal, utilization of hydrocarbons with proper representation of actual constituents of real fuels is one of the most critical requirements. The major goal of this paper is to identify hydrocarbons that have a great potential to advance the current gasoline surrogates in terms of emulations in hydrocarbon class composition and combustion related properties, and to promote further experimental and computational investigations for those hydrocarbons. In this paper, 19 hydrocarbons including the ones that have not been used for gasoline surrogate applications are assessed through an optimization approach. Surrogate mixtures are formulated for petroleum-derived gasoline fuels using new hydrocarbons along with conventional gasoline surrogate components (n-heptane, iso -octane, toluene, 1-hexene), and potential improvements in target property emulations by addition of the new surrogate components are evaluated. Among four hydrocarbon classes investigated in this study which are iso -alkane, cycloalkane, aromatic, and olefin, optimized results indicate that expanding iso -alkane representation by using multiple iso -alkane components with different molecular size is the most effective approach to emulate various target properties of typical gasoline batches. Also, among 19 new hydrocarbons tested, 2-methylbutane appears to be a favorable option for a small iso -alkane, 2, 2, 3, 3-tetramethylhexane for a large iso -alkane, cyclopentane for a cycloalkane, and 1, 2, 4-trimethylbenzene for a large aromatic. With a new surrogate palette that includes these promising hydrocarbons, surrogate mixtures are formulated for 5 different batches of gasoline, which shows capabilities to emulate composition characteristics and target properties tested, including knock resistance and distillation curve.